PENGARUH UKURAN PERUSAHAAN, LEVERAGE, LIKUIDITAS, PROFITABILITAS, DAN PERTUMBUHAN LABA TERHADAP KUALITAS LABA (Studi Empiris Pada BUMN yang Listing di Bursa Efek Indonesia Periode 2013-2017) - Mulyaningsih Retri; Surya Satriawan R. Adri; Julita Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the effect of company size, leverage, liquidity,profitability, and profit growth on the quality of earnings on BUMN that are listed on theIndonesia Stock Exchange in 2013-2017. The population in this study were BUMN listedon the Indonesia Stock Exchange in the period 2013-2017, with a purposive samplingtechnique obtained by 11 companies as samples. The dependent variable used in thisstudy is the quality of earnings. Independent variables are company size, leverage,liquidity, profitability, and profit growth. The analytical method used in this study ismultiple linear regression analysis using the help of IBM SPSS Statistics 24.0. The resultsshowed that firm size has no effect earnings quality at P> 0.05 (P = 0.846). Leverage hasno effect earnings quality at P> 0.05 (P = 0.695). Liquidity has no effect on earningsquality at P> 0.05 (P = 0.498). Profitability has effect on earnings quality at P <0.05 (P= 0.008). And profit growth has no effect on earnings quality at P> 0.05 (P = 0.164).Keywords : company size, leverage, liquidity, profitability, profit growth, and earningsquality